Alpha-cluster structure of light nuclei 14C, 14N, AND 14O - Grinyuk, Boris; Piatnytskyi, Dmytro; Vasilevsky, Victor (XХХII Щорічна наукова конференція Інституту ядерних досліджень НАН України, 2025)
A method is developed to solve the quantum few-body problem for the bound states [1 - 3]. In the framework of the variational method in the Gaussian representation, the structure characteristics of light nuclei 14C, 14N, and 14O are studied within the five-cluster model (three α-clusters plus two extra nucleons). Specific properties of the charge density distributions, form factors, pair correlation functions, and the momentum distributions of these nuclei are analyzed. Within a similar approach, form factors and density distributions of 12C, 16O, and 20Ne nuclei are calculated in the framework of the α-cluster model.